Construction of a hologerencial tripod for university communities (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This article was aimed at the theoretical construction of a hologerencial tripod for academic communities in higher education, from the innovative management approaches and strategies as stated by Drucker (1997), conceived as the management and the specific organ of any organization . Methodologically the research was framed within the qualitative paradigm of post-positivist nature, under the phenomenological hermeneutical method. As information gathering technique was used in-depth interview applied to five key informants, providing between one of its findings the need for management based in knowledge and humanism, through a distributive leadership. We conclude that there is a need to address the university management drivers.
Keywords: academic communities; college education; management strategies; innovation; university management